"I Pray That We Will Find a Way to Carry on This Dream": How a Law Enforcement Crackdown United an Online Community. (July 2019) - Ladegaard, Isak
Durkheim claimed that punishment of crime generates social cohesion as "honorable" people are united in emotional, passionate condemnation of those who transgress society's moral boundaries. This study examines reactions to punishment in the punished group. Specifically, it examines how members of an online community responded when law enforcement shut down their websites. Drawing on data from three discussion forums, the author argues that the crackdown produced solidarity and enhanced a particular moral worldview that strengthened the community and enabled it to survive by migrating en masse to new websites.